Tribological performance enhancement of rapeseed biolubricant using modified eichhornia crassipes nanoparticles additive - Opia, Anthony Chukwunonso (2022)
Lubricant additives are substances that are used in reducing friction and wear between two or more moving components. They are chemically, partially, or mechanically produced with the aim of controlling friction and wear during sliding contact. Various functional vegetable lubricants have been developed with narrow views of the environmental impact issue due to the use of fossil-based additives in the formula. These lubricants can be made more sustainable by using all environmentally friendly and renewable base stock items. However, few researchers, who took these factors into account, emphasised the use of biomaterials in the lubricant additive formulations mainly because of the challenges in their physicochemical characteristics. Eichhornia Crassipes (EC) have been used for industrial applications such as sorbent and bio-fuel, but application in lubrication additive is rarely reported in the literature. Therefore, in this study, EC, a pure aqua bio-plant, was used to enhance the base lubricant performance for lubrication application, based on the most desirable lubricant additive qualities validated by characteristic tests and good compatibility due to their similar functional groups. For the development of EC carbon nanotubes (EC-CNT) that provide anti-wear service, the formulation uses a mechanical approach of ball milling and a cyclic heating method. Synthetic technique was used to develop the EC Carboxymethyl cellulose (EC-CMC) polymer. The novel EC-additives were formulated to improve to improve the tribological qualities and shear stability requirements of the base lubricant. The tribological studies were conducted using a high frequency reciprocating test rig and a unidirectional ball on disc tribo-tester. The final EC-additive package was chosen after optimal concentration study. This indicated that 1.2 wt. % EC-CNTs + 0.4 wt. % EC-CMC yielded the best performance. The formed nanofluid, which contains 98.4 % base lubricant and 1.6 wt.% EC-additives (1.2 wt.% EC-CNTs + 0.4 wt.% EC-CMC) as the additive package, has a coefficient of friction (COF) of 0.08 and average wear scar diameter (WSD) of 54.1 μm on High Frequency Reciprocating Rig (HFRR), better than unidirectional mode. EC-additive results under HFRR were compared to commercial Zinc Dialkyl Dithiophosphate (ZDDP) as a benchmark (COF = 0.07, WSD = 48.3 nm), which were found to be substantially similar. The good performance of EC-additive under HFRR mode was due to little starvation of lubricant at the contact region. Under HFRR mode, better surface protection was achieved while under unidirectional mode yielded severe surface wear due to much lubricant starvation at the contact surface. Shear stability tests of the new EC-additive and the commercial ZDDP were performed for a range of 10 to 1500 1/s shear rate 25oC to 75oC temperature. The test results showed that the novel EC-additive has better shear stability than ZDDP, which could be attributed to the presence adequate polymer. Repassed oil blended EC-additives that can improve tribological performance of a vegetable lubricant during sliding contact lubrication have been successfully developed. This research proved that the performance of the base lubricant can be enhanced by using the novel EC-additive formulated from a pure aqua bio-plant. This means that EC-additive has the potential to effectively replace fossil-based additives for lubrication operation within the tested capacity, resulting in an ecologically sustainable, renewable and good tribological performance.